Rancang Bangun Sistem Informasi Layanan Pengajuan Surat Keterangan Berbasis Website Menggunakan Metode Extreme Programing - Novia Agus Mila (Swarnadwipa, 2024)
The Sinar Sekampung Village Office conducts conventional certificate submission activities, where people who want to submit a certificate must come directly to the village office and fill out the file completeness form, the village office officer will check the completeness of the file, and the village head will sign the letter, the archive data for the letter submission is stored in the file cabinet causing several obstacles, namely the accumulation of files, This greatly affects the performance of services at the village office to be less effective and efficient, for this reason, as an effort to overcome these problems, a website-based certificate service system will be built to help village office officers and also the community who will submit certificates. Information system development is carried out using the Extreme programming method by covering the stages of planning, design, coding and testing. The system is designed using UML (Unified Modelling Language) and built using a Mysql database with PHP programming language implementing the codeigniter framework. Testing on this system uses ISO 25010 testing in terms of functionality and usability, the results obtained are 98.25% so that this system is included in the Very Good criteria, based on these results, it can be concluded that this system has software feasibility quality that is comfortable to use by users and is able to improve certificate services at the Sinar Sekampung Village Office with a website-based.